The Politics of Laughter in the Social Media Age
XXI, 314 p. 10 illus.
Keywords: “An original and sophisticated collection on laughter and ridicule in the global south in the age of digital media. This is a hard headed take which is as much about the robust ridiculing of the pretensions of postcolonial regimes, as about the dangers of the accelerated dispersion of prejudice and stereotype. A timely and exigent intervention”. - Dilip M Menon, Mellon Chair in Indian Studies, Director Centre for Indian Studies in Africa "This is a superb volume of essays on the subject of laughter and ridicule as it is deployed to mock and put pressure on rogue postcolonial regimes by concerned citizens, with social media tapped into as a rich reservoir of political struggles and contestations between the powerful and the powerless! In this volume, laughter and ridicule emerge as a method and indeed a discourse of speaking truth to power." - Sabelo J. Ndlovu-Gatsheni, Professor and Chair of Epistemologies of the Global South & member of the Africa Multiple Cluster of Excellence, University of Bayreuth, Germany The Politics of Laughter in the Social Media Age: Perspectives from the Global South brings to critical and intellectual attention the role of humour in the digital era in the Global South. Many citizens of the Global South live disempowered and precarious lives. Digital media and humour, as chapters in the volume demonstrate, have empowered these citizens through engagement with power and their peers, enabling a pursuit of a better future. Contributors to the volume, while alive to challenges associated with the digital divide, highlight the potentials of social media and humour to engage and seek redress on issues such as corruption, human rights violations, racism and sexism. Contributors expertly analyse memes, videos, cartoons and other social media texts to demonstrate how citizens mimic, disrupt, ridicule and challenge status quo. This book caters for academics and students in media and communication studies, political studies, sociology and Global South studies. Shepherd Mpofu is Associate Professor in Media and Communications at the University of Limpopo, South Africa. He is an African Humanities Programme Fellow. He is co-editor of Mediating Xenophobia in Africa (Palgrave, 2020). He regularly publishes in academic journals on themes such as media and identity, media and protests, gender and race.